The Moderating Role of Gender in the Relationship Between Service Quality Dimensions, Word-of-Mouth Advertising, and Purchase Intention - Rasouli , Mona; Gholipour Fereidooni, Shahrbanoo; Rouholamini, Mehdi (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective:  The aim of this study is to assess the impact of electronic service quality dimensions on customer purchase intention, with the mediating role of electronic word-of-mouth advertising and the moderating role of gender.Methodology:  This applied research is descriptive in nature, and the statistical population includes customers of Bank Melli branches in Tehran province who use the electronic services of the Bank Melli Bam system. Based on the cluster sampling method and according to the Morgan table, the sample size was estimated to be 384 individuals. Standard questionnaires were used for data collection, and structural equation modeling based on the partial least squares approach was used for data analysis with the statistical software Smart PLS3.Findings: The findings of the study indicate that the four dimensions of service quality have a positive and significant impact on electronic word-of-mouth advertising. Additionally, the positive and significant impact of electronic word-of-mouth advertising on customer purchase intention was confirmed, and the mediating role of electronic word-of-mouth advertising in the relationship between service quality dimensions and customer purchase intention was verified. Furthermore, by examining the moderating role of gender in the relationship between electronic word-of-mouth advertising and purchase intention, it was found that women are more likely than men to make purchases through electronic word-of-mouth advertising.Conclusion: Overall, it can be concluded that enhancing the quality dimensions of services leads to the formation of word-of-mouth advertising among customers, which can influence customer purchase intention. The value and innovation of the present study lie in the simultaneous examination of the three variables of electronic service quality, word-of-mouth advertising, and purchase intention, considering the qualitative moderating variable of gender.